2021
DOI: 10.1021/acs.nanolett.1c02331
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Mechano-thermoelectric Heterojunctions for Self-Powered Strain Sensors

Abstract: We here demonstrate the multifunctional properties of atomically thin heterojunctions that are enabled by their strong interfacial interactions and their application toward self-powered sensors with unprecedented performance. Bonding between tin diselenide and graphene produces thermoelectric and mechanoelectric properties beyond the ability of either component. A record-breaking ZT of 2.43 originated from the synergistic combination of graphene’s high carrier conductivity and SnSe2-mediated thermal conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…Apart from graphene, its derivatives, and MXene, other emerging 2D nanomaterials such as MoS 2 , 145,146 indium selenide (In 2 Se 3 ), 122,147 stannous sulfide (SnS), 100,148 tin diselenide, 149 vanadium nitride (VN), 123 and tin disulfide (SnS 2 )/SnS 150 have great potential in the field of flexible sensors as well, especially in tactile sensing. Hu et al 122 reported a class of 2D layered materials with an identical orientation of in-plane polarization whose piezoelectric coefficients (e 22 ) increased with layer number, thereby allowing the fabrication of flexible piezotronic devices with large piezoelectric responsivity and excellent mechanical durability (Figure 4F).…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…Apart from graphene, its derivatives, and MXene, other emerging 2D nanomaterials such as MoS 2 , 145,146 indium selenide (In 2 Se 3 ), 122,147 stannous sulfide (SnS), 100,148 tin diselenide, 149 vanadium nitride (VN), 123 and tin disulfide (SnS 2 )/SnS 150 have great potential in the field of flexible sensors as well, especially in tactile sensing. Hu et al 122 reported a class of 2D layered materials with an identical orientation of in-plane polarization whose piezoelectric coefficients (e 22 ) increased with layer number, thereby allowing the fabrication of flexible piezotronic devices with large piezoelectric responsivity and excellent mechanical durability (Figure 4F).…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…2D materials with a dangling-bond-free van der Waals structure break the limitation of the lattice-matching condition of heteroepitaxial growth and thus are promising candidates for vertical heterostructures. , The growth of TMD-based vertical heterostructures has been intensively developed in the past few years, including TMD/graphene, TMD/h-BN, , TMD/perovskite, , TMD/iodide, , TMD/TMD, etc. Among them, TMD/TMD is worthy of great attention, as TMDs with a wide range of band gaps enable heterojunctions with distinct interfaces to be obtained, including metal–metal, semiconductor–semiconductor, and semiconductor–metal, adapting the requirements of diverse electronics and optoelectronics.…”
Section: Controllable Cvd Growth Of Tmd Heterostructuresmentioning
confidence: 99%
“…reported on self‐powered strain sensors based on piezoelectric and thermoelectric energy harvesting. [ 1109 ] By combining the mechanoelectrical and thermoelectric properties of SnSe 2 and graphene heterostructures, the device achieved a record ZT value of 2.43 and functions as a strain sensor by measuring the variation of the output thermoelectric current. [ 1109 ] Wang et al.…”
Section: D Materials Based Wearable Energy Harvesting Technologiesmentioning
confidence: 99%
“…[ 1109 ] By combining the mechanoelectrical and thermoelectric properties of SnSe 2 and graphene heterostructures, the device achieved a record ZT value of 2.43 and functions as a strain sensor by measuring the variation of the output thermoelectric current. [ 1109 ] Wang et al. also established the self‐powered pressure sensor capability of MXene‐enhanced PENG.…”
Section: D Materials Based Wearable Energy Harvesting Technologiesmentioning
confidence: 99%